2020
DOI: 10.1097/md.0000000000020517
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative methicillin resistant Staphylococcus aureus results do not predict surgical site infections in children undergoing varus derotational osteotomy

Abstract: Literature regarding the value of pre-operative nasal methicillin resistant Staphylococcus aureus (MRSA) swabs to predict surgical site infections (SSIs) in children undergoing lower extremity surgery is limited. The purpose of our study was to determine if pre-operative nasal MRSA swab results were predictive of SSI development in children undergoing a femoral varus derotational osteotomy (VDRO). Patients who underwent VDRO between 2004–2016 were reviewed to determine pre-operative MRSA colonizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…In the present study, the prevalence of MSSA and MRSA nasal carriage was 13.1% and 0.3%, respectively, rates that are much lower than those reported in previous studies (Herrmann et al, 2013;Kondo et al, 2020;Nazareth et al, 2020;Reid et al, 2017;Vos et al, 2009). The discrepancy may be due to differences in patient baseline characteristics.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…In the present study, the prevalence of MSSA and MRSA nasal carriage was 13.1% and 0.3%, respectively, rates that are much lower than those reported in previous studies (Herrmann et al, 2013;Kondo et al, 2020;Nazareth et al, 2020;Reid et al, 2017;Vos et al, 2009). The discrepancy may be due to differences in patient baseline characteristics.…”
Section: Discussioncontrasting
confidence: 87%
“…MRSA infection has become a global problem, and these infections have been associated with worse outcomes. The reported prevalence of MRSA nasal carriage in patients undergoing surgery ranges between 1.5% and 9.4% (Herrmann et al, 2013;Kondo et al, 2020;Mizuno et al, 2019;Munoz et al, 2008;Nazareth et al, 2020;Vos et al, 2009). The prevalence of MRSA nasal carriage in Japanese patients undergoing colorectal surgery was 3.4% (Kondo et al, 2020), whereas the prevalence of MRSA nasal carriage in Spanish patients undergoing cardiac surgery was as high as 9.4% (Munoz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was 247-356 people. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] The examined data revealed that MRSA-positive had a significantly higher SSI compared with MRSA-negative in SS subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 247 children undergoing varus derotation osteotomy, Nazareth et al (2020) found 2% positive MRSA swab tests. The MRSA nasal swab test is routinely used as a pre-operative screening method based on the assumption that the results will influence the treatment management and decrease the surgical site infections rates [15]. To determine pre-operative MRSA colonization status, Nielsen et al (2018) presented a retrospective chart review of patients after posterior spinal fusion performed between 2004 and 2014, and identified 2.3% MRSA-positive cases [16].…”
Section: Discussionmentioning
confidence: 99%